Uji Performa Termoelektrik pada Generator Air Cooler - Makmur Saini; Sonong Sonong; Aslan Afif; Suhartiwi Suaib (Politeknik Negeri Ujung Pandang, 2021)
Generator Air Cooler (GAC) is an important part of the hydropower system which is used to cool the air in the generator room. GAC is a form of application of a heat exchanger (heat exchanger) with water as a coolant. There is a difference in air temperature before and after the GAC, so presumably it can be utilized by using a thermoelectric which is expected to work well as a coolant, in this case it takes into account its ability to absorb heat as a thermoelectric input and generate electrical energy as its output. From the test results, the addition of a thermoelectric was able to increase the effectiveness and NTU and also reduce LMTD. The effectiveness of the resulting GAC without thermoelectric addition yielded 89.90%, 91.85%, and 91.51%. Meanwhile, if the thermoelectric is added, it is 91.39%, 92.82%, and 92.58%. The electric power generated from three days of thermoelectric testing was 0.022W, 0.019W, and 0.021W, with an efficiency of 6.44%, 5.18%, and 4.07%.